L.A. Outlaws : A Novel - Parker, T. Jefferson (New York Signet, 2009)
Investigating the latest crime scene of a celebrity thief who has been staging lucrative heists and donating the spoils to charity, rookie deputy Charlie Hood is forced to make an ethics-testing decision when the thief is targeted by a professional killer.
Keywords: Police -- California--Los Angeles -- Murder--Investigation -- Detective and mystery stories